Kajian Fisis Optimalisasi Daya Bateray Lithium dalam Pengaruh Deformasi - Safaruddin A Prasad; Jufra Jufra; Akhiruddin Maddu (Radial : Jurnal Ilmiah Sains dan Rekayasa, 2023)
Simulations have been carried out of equal power for lithium batteries with one-way diffraction grating deformation using magnetic induction coils which are converted into heat energy to heat a certain volume of water. The heating time was observed from the initial temperature of 30 degrees Celsius to the final temperature of 100 degrees Celsius for each coil length L. Using multiple linear regression analysis, a power change ratio of 0.95 was obtained. This means that the battery power will increase by 0.05 or 5 percent if it is treated with a compressive force to the limit of elasticity. This is possible because Lithium has a Young's modulus of 4.9 GPa, a shear modulus of 4.2 GPa, and a bulk modulus of 11 GPa.